The view from space: Theory-based time-varying distances in the gravity model - Julian Hinz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
I compute distances used in the gravity model of international trade that improve the existing measures along multiple lines and help remedy the border puzzle by up to 50%. I derive a trade cost aggregation that is agnostic to the underlying gravity framework while taking into account the economic geography of countries. Using this method I compute bilateral and internal country distances, making use of nightlight satellite imagery for information on the economic geography of countries.
Keywords: F10; F14; 330